Project Successful Deployment: A Method for Evaluating the Success of Digitalization Projects - Romagnoli, Giovanni; Esposito, Giovanni; Reverberi, Davide (International Journal of Online and Biomedical Engineering (iJOE), 2022)
In this paper, we present a method for evaluating the success of digitalization projects, namely the Project Successful Deployment (PSD). With the term digitalization, we mean the use of digital technologies and digitized information to create value in new ways and to benefit from them. The existing methods for project evaluation emphasize the capability of a project to deliver its results by respecting times and costs. The method we propose, instead, suggests evaluating projects by means of its external dimensions, namely the functionalities and quality of the deliverables. These external project dimensions are reflected on the project scope, and thus evaluate the requirements of the deliverables, and the degree to which the deliverable meet their quality objectives The method is composed of a set of matrixes, and it uses a structured procedure to define and refine its items and their weights, by means of a panel of experts. It has been applied to a practical case study, a digitalization project of a network of research and teaching laboratories. The method allowed a structured project evaluation, and the practical case study showed strengths and weaknesses of the PSD model, which proved to be robust and effective, in providing a timely evaluation of the project.